Land Revegetation Post Clay Mine PT Semen Baturaja (Persero) Tbk in OKU Selatan District "Challenges for Environmental Sustainability" - Marwan Sastradinata (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2018)
Clay as a non-renewable natural resource causes the number of reserves to be a limiting factor for mine age. The post-mining plan is prepared as an effort to restore the physical and environmental conditions that are disturbed by mining. Data collection was carried out with location surveys, literature studies, and institutional coordination. Mine reserves are known to be 36 million tons with a thickness of up to 25 m. The clay chemical composition consisted of SiO2 12.77% -92.49%, Al2O3 2.95% -27.64% and Fe2O3 0.53% -29.46%. The environment disturbed by post-mining will be managed with 39.5 ha of plantation designation, 13.5 ha of forestry and 1.7 ha of water treatment. Natural vegetation consists of secondary forests, shrubs, resident gardens. The diversity index value of the bush species of 2.940 is dominated by 15 plant species. Distribution of evenly distributed plants such as medang, aro wood, krinjing. Vegetation of cultivated plants is dominated by 10 types of plants such as coffee, pepper, rubber. Revegetation stage in the form of cover crop sowing, nurseries and the development of fast-growing plants. Post-mining revegetation uses plants that have suitable soil conditions so that environmental improvements and environmental sustainability of clay mines are achieved.